The meaning of the social support network for women in situations of violence and breastfeeding - Nayara Girardi Baraldi; Angelina Lettiere-Viana; Diene Monique Carlos; Natália Rejane Salim; Daniela Taysa Rodrigues Pimentel; Juliana Stefanello (Universidade de São Paulo, 2020)
Objective: to understand the meanings attributed to the social support network of women breastfeeding and in situations of violence by an intimate partner. Method: a qualitative study, carried out with 21 women, through semi-structured interviews and data analyzed by the Method of Interpretation of the Senses in the light of the conceptual framework of Social Support Network. Results: all women suffered violence by the partner in the puerperium and only one of them maintained exclusive breastfeeding until 180 days postpartum. In the analysis, the category entitled "The action of the social support network in the face of breastfeeding in the context of intimate partner violence" emerged, with two subcategories: "Interpersonal support network" and "Institutional support network". In the interpersonal network, the partner was little mentioned, on the other hand, there was a greater participation of other women. In the institutional network, non-resolution and actions centered on biological character were evident. Conclusions: the search for help in the interpersonal network stood out in comparison to the institutional network, both with regard to the issue of violence and breastfeeding and the actions related to it, mostly ineffective, characterized by counseling and referrals.